Energy infrastructure for decarbonizing other energy sectors through renewable electricity - a spatio-temporal analysis from useful energy demand to renewable energy supply of sector coupling pathways based on the German case - Christina Kockel; Lars Nolting; Jan Priesmann; Aaron Praktiknjo (Asian Development Bank Institute (ADBI), 2020)
While progress in reducing greenhouse gas emissions is notable in the power sector, other sectors such as transportation and often heating are lagging behind. A strategy to propagate greenhouse gas emission reductions from the power sector to other sectors is so-called "sector coupling." Against this backdrop, we ask the following two questions: (1) To what extent does demand for (useful and final) energy match the supply of renewable energy sources in the dimensions of time and space? (2) What impacts of sector coupling pathways on future infrastructure requirements can be derived from applying spatiotemporal analyses? For our analyses, we assume a scenario with 95% greenhouse gas emission reductions for Germany as a case study as targeted by the government for 2050. We choose a consumer-driven approach, analyzing the energy value chain backwards from consumption to supply for the different sector coupling technologies. From useful energy consumption, we derive final energy demand patterns in high temporal and regional resolution and evaluate implications for different strategies of renewable energy expansion. The key contributions of our study are twofold: First, we introduce a generalizable and transferable consumer-driven analysis in high temporal and regional resolution for energy systems with high degrees of sector coupling and derive implications for the energy infrastructure. Second, we provide policy recommendations from our results regarding effective and efficient strategies for the integration of renewable energy sources into present energy systems.
Keywords: C23; C5; C63; Q4; 330; sector coupling; renewables; electricity; heating; transportation; infrastructure; energy policy